Tinjauan Pastoral Kepada Anggota Jemaat Atas Sikap Tidak Menetap Denominasi Gereja di Jemaat GMIM Bethesda Taas Wilayah Manado Timur IV - Luas, Luosje Treesje; Macarau, Betania Petrya Truce (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2022)
There are not a few church denominations in the world, but there are a lot of them. Talking about church denominations, it is a Christian religion that is formed in one organization that exists regarding leadership, ways of worship and congregations working or trying to work together hand in hand without tearing each other down to achieve goals or cohesiveness within an existing organization. Many Church Denominations exist and we have the right to choose and make decisions about where we will be registered in a Church Denomination. However, this does not mean that we are registered in two Church Denominations at will or as we please. This research uses quantitative methods. The purpose of this research is to inform congregation members to be able to make existing decisions and settle in one church denomination. It is hoped that the results of this research will provide understanding to congregation members not to join two church denominations and provide pastoral assistance as well as pastoral review for congregation members who follow two church denominations.